The Old Place : a novel - Finger, Bobby (New York : G. P. Putnam's Sons, 2022)
"A bighearted and moving debut about a wry retired schoolteacher whose decade-old secret threatens to come to light and send shockwaves through her small Texas town"--.
new book 2022 fall.
Keywords: Bereavement; Retired teachers; Female friendship; Secrecy; Pastoral fiction; Novels